1995
DOI: 10.1128/mcb.15.12.6932
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Latent Transforming Growth Factor β1-Binding Protein 2: Molecular Cloning, Identification of Tissue Isoforms, and Immunolocalization to Elastin-Associated Microfibrils

Abstract: Monoclonal antibodies to fibrillin 1 (MP340), a component of elastin-associated microfibrils, were used to screen cDNA libraries made from bovine nuchal ligament mRNA. One of the selected clones (cL9; 1.2 kb) hybridized on Northern (RNA) blotting with nuchal ligament mRNA to two abundant mRNAs of 9.0 and 7.5 kb, which were clearly distinct from fibrillin mRNA (10 kb). Further library screening and later reverse transcription PCR by the rapid amplification of cDNA ends (RACE) technique resulted in the isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
143
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 35 publications
2
143
1
Order By: Relevance
“…67-kDa cell surface elastin-binding protein (35); the elastinmicrofibril interface protein emilin (36); the fibrillin-like latent transforming growth factor B-1 binding proteins (37,38); and the small dermatan sulfate proteoglycans decorin and biglycan (13,14). Recently Trask et al (13) demonstrated the importance of sulfation for the assembly of elastin, fibrillin-1, and MAGP-1 into extracellular matrix, and this finding suggested that a proteoglycan(s) is involved in elastic fiber assembly.…”
Section: Discussionmentioning
confidence: 99%
“…67-kDa cell surface elastin-binding protein (35); the elastinmicrofibril interface protein emilin (36); the fibrillin-like latent transforming growth factor B-1 binding proteins (37,38); and the small dermatan sulfate proteoglycans decorin and biglycan (13,14). Recently Trask et al (13) demonstrated the importance of sulfation for the assembly of elastin, fibrillin-1, and MAGP-1 into extracellular matrix, and this finding suggested that a proteoglycan(s) is involved in elastic fiber assembly.…”
Section: Discussionmentioning
confidence: 99%
“…10 LTBP, initially identified as part of the large latent TGF-␤ complex, 11 is a component of the ECM of various cell types and tissues. [12][13][14] Although LTBP does not directly mediate the latency of TGF-␤, 15 it is known to be important for the assembly and secretion of the complex, 6 and additionally for the storage of TGF-␤ in the ECM. The release of latent TGF-␤ from ECM by proteolytic cleavage of LTBP is discussed to be an initial step in the activation of TGF-␤.…”
mentioning
confidence: 99%
“…Thus, LTBPs are supposed to be important constituents of the microfibrillar structure of connective tissue. [23][24][25] The presence of LTBPs in parenchymal and nonparenchymal liver cells and its proposed biological functions prompted us to investigate in some detail the expression of LTBP isoforms in experimental fibrosis and transdifferentiating cultured rat HSC. In addition, the time-dependent binding of TGF-␤ components (LTBP, LAP, TGF-␤) to the extracellular matrix and possible biological functions of LTBP in cultured transdifferentiating HSC were studied.…”
mentioning
confidence: 99%